Analysis of training means for jumpers and jumpers in horizontal jumps - Salamatov M.B., (Theory and Practice of Physical Culture, 2024)
Due to the difficult geopolitical situation in the world, Russian sport is going through a critical period. Currently, Russian athletes are under sanctions imposed by the Olympic Committee. In conjunction with the above, there is a decline in sports achievements and sports performance of highly qualified jumpers, since they cannot compete at the Olympic Games and World Championships. To improve technical preparedness, and therefore the effectiveness of competitions, experts strive to develop new training methods. The purpose of the study was to analyze the means of preparing jumpers and jumpers in horizontal jumps.